ANALISIS PENYERAPAN TENAGA KERJA PADA INDUSTRI GENTENG DI KECAMATAN GANDUSARI KABUPATEN TRENGGALEK - Lely Diyah Ayuningtiyas; Mohammad Faisal Abdullah; Muhammad Sri Wahyudi Suliswanto (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
The purpose of this study is to examine the influence of the number of industries, labor wages, and the amount of production toward the employment in tile industry in Gandusari, Trenggalek. The method of this study is quantitative research method with a statistical data retrieval using some calculations and hypothesis testing. Sampling using a cluster sampling technique. The classical assumption test, multiple linear regression analysis, and the regression coefficient significance test were carried out as the data analysis technique. The result of the partial model test reveal that the number of industries had a significant impact on the employment. Meanwhile, the labor wages indicate a negative significance impact on the employment. The amount of the production has a significant impact on the employment in tile industry. The simultaneous model testing reveals that the number of industries, labor wages as well as the amount of production have really significant effect on the employment.